Diplomatic privileges and immunities in a new millennium: a critical analysis of the Vienna Convention on Diplomatic Relations 1961 - Megne, Loreta (Riga Graduate School of Law, 2020)
21st century is described as the age of changes and technologies. Therefore, changes are also experiencing diplomatic law, in particular the Vienna Convention on Diplomatic Relations. The Convention was signed in 1961, in the previous century. Since then, many things have changed, including priorities for each state. The Convention regulates diplomatic relations between states, and it specifically entitles diplomatic agents to the diplomatic immunities and privileges, which includes inviolability and immunity from prosecutions. Some of the Articles do not correspond to our times. Firstly, because technologies have evolved changing the nature of diplomatic correspondence and diplomatic bag. Secondly, some Articles are too broad and requires some limits or more specific explanation for specific terms.